CFD Analysis of Petrol Internal Combustion Engine (Journal of University of Babylon for Engineering Sciences, 2018)
Optimizing operation for internal combustion engines requires the application of advanced essential technique. Moreover, an experimental investigation, numerical 3D CFD simulation, is needed in order to obtain and investigate a vision into the complex phenomena’s within cylinder. In this paper, fluid flow inside a single cylinder of spark ignition engine (SI) Hyundai type was modeled depending on the numerical simulation using ANSYS V15.0/ICE CODE, with dynamic mesh technique to study and estimate the characteristics flow under normal operation of octane fuel with respect to crank angle at a constant r.p.m. The engine model was done by SolidWorks environment. This work focused on the simulation of the intake, compression, expansion and exhaust stroke, including cold and combustion simulation, solving the governing equations (continuity, Renolds Average Navier Stoke, and energy equation). The code was validated against published data for present case, and the comparison showed a close agreement between the results and the maximum discrepancy was 17 %.